A formative evaluation of the UCT PMD Programme - Velloo, Ilhaam (Institute for Monitoring and Evaluation, 2018)
Personal mobile devices (PMDs) such as tablets (also referred to as tablet computers or tablet pc) have become important educational technology components for university students. Although advances in wireless, mobile technology have resulted in PMDs becoming widely available and less expensive, PMD ownership still presents a substantial capital outlay beyond the means of many South African university students. Thus, there is a need to explore the opportunities low cost PMD initiatives present. Thus far, limited research has been conducted on if and how flexible learning is achieved through low cost PMDs in the South African higher education context, where access to technology and internet access is inconsistent amongst the student population. This study aims to evaluate the outcomes of the PMD Programme at the University of Cape Town (UCT). The programme aims to create a flexible teaching and learning environment for students in higher education, through the use of low cost tablets. This study focused on whether the programme's short‐term outcomes, namely, improved mobile technology knowledge, portability, mobility, communication, information sharing and collaboration were achieved. The extent to which the programme's medium‐term goals (digital literacy and access to course information) were achieved, were also investigated. Lastly, the degree to which students believed the low cost tablet was good enough for their studies was assessed. This evaluation found that the UCT PMD Programme plays a crucial role in providing students with access to affordable mobile technology in the form of low cost tablets and has demonstrated enhancement of students' ability to learn in a flexible manner. The UCT PMD Programme facilitated improvement in students' mobile technology knowledge, mobility of learning and portability of information immensely. Improved communication and collaboration between peers and lecturers were noted. Information sharing was not enhanced through the use of the tablet. Students' digital literacy skills increased and access to information improved immensely through using the tablet. Overall, through the use of the tablet, improvement in students' flexibility of learning was achieved and students found the low cost tablet adequate for their studies.